Influence of amount of feed offered on growth, intake and selectivity: Observations on sheep and goats - Aboud, A.A.O.; Owen, E.; Reed, J.D.; Said, A.N. (International Livestock Centre for Africa, 1993)
Comparisons were made between 24 Ethiopian rams and 24 Galla goats for voluntary intake, feed selectivity and growth performance when offered three levels of sorghum stover. The levels observed were 25,50 and 75 g/kg live weight per day. Measurements of intake, growth and feed selectivity were taken over a period of 10 weeks.